Seroprevalence of Rickettsial infections in rats in the Upper South of Thailand - Thongkhao, Kanaphot; Rodkvamtook, Wuttikon; Sukra, Kotchapan; Ninsaeng, Ubolrat; Jidkaew, Thasanee; Atta, Yuppayong; Poolprasert, Pisit (Disease Control Journal, 2023)
This study aimed to investigate the species and infection rate of rickettsioses from rodents in the upper south of Thailand. Rats were trapped and their serum samples were collected in order to detect the IgG antibody using indirect immunofluorescence assay (IFA) technique. From all of 1,050 traps, 124 traps were successful for rat capturing, which accounted for 11.81%. Twelve rodent species were identified morphologically. Rattus tanezumi was the most abundant species (70.97%), followed by Bandicota indica and Maxomys surifer (6.45%), Sundamys muelleri and Niviventer fulvescens (4.03%), R. tiomanicus and Maxomys whiteheadi (1.61%), Mus musculus castaneus, R. argentiventer, R. sladeni, N. langbiansis and Hylomys suillus siamensis (0.81%). Rickettsial infection rate was 37.90%. Based on IgG antibody tests performed on 124 serum samples, IgG antibody to scrub typhus was detected in 37.90% of the samples, whereas IgG antibody against tick typhus was observed in only 1.61% of the samples. However, no IgG antibody to murine typhus was detected. During this study, identification of tick-borne rickettsial infection, another form of scrub typhus, was of special interest. To address the issue, surveillance of scrub typhus in rodents and other potential hosts should also be carried out. In addition, biology of vectors like chiggers and ticks should be explored so that the results could be used as basic information for predicting disease incidence in the area. Besides, we can educate people on how to protect themselves if they have to travel to high-risk areas where incidence of rickettsial infections in animal reservoirs is discovered.